2013
DOI: 10.1002/poc.3097
|View full text |Cite
|
Sign up to set email alerts
|

Tautomeric populations of the charged species of 1,12-diamino-3,6,9-triazadodecane (SpmTrien) studied with computer simulations and cluster expansions

Abstract: Correct net charge and protonation pattern in the polyamine backbone is one of the major factors that define the interactions of this class of compounds. 1,12‐diamino‐3,6,9‐triazadodecane (SpmTrien) is a isosteric charge deficient analogue of naturally occurring spermine (Spm) with different biological features. The tautomeric populations of each SpmTrien charge state were estimated with computer simulations, molecular dynamics (MD) and quantum mechanical calculations, and cluster expansions separately. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Also, one must realize that the obtained 40:60 ratio must not be taken literally as it must depend on a solvation model as well as level of theory used (we found e.g., 1% and 54% of HL p from modelling at HF and B97D level of theory, respectively) and, unfortunately, there is no easy way to rigorously verify any theoretical model experimentally. In support of this, Weisell et al [44] found, from QM-modelling of pentamine 1,12-diamino-3,6,9-triazadodecane (SpmTrien) involving explicit water molecules, that 91% (HL p ) and 9% (HL s ) is formed with short chain being protonated preferentially (66% short and 25% long chain for the HL p form) which clearly contradicts all earlier as well recent studies whereas from the CEA of NMR data they obtained 94% (HL p ) and 6% (HL s ) with long chain, as expected, being protonated preferentially, ~84%. Moreover, note that their findings, in general, are not in agreement with other studies as they predicted a very small fraction of HL s whereas this tautomer was found to be significant in many polyamines and even dominating, e.g., in spermine [5,8,41].…”
Section: Theoretical Prediction Of Protonation Sequencementioning
confidence: 79%
See 1 more Smart Citation
“…Also, one must realize that the obtained 40:60 ratio must not be taken literally as it must depend on a solvation model as well as level of theory used (we found e.g., 1% and 54% of HL p from modelling at HF and B97D level of theory, respectively) and, unfortunately, there is no easy way to rigorously verify any theoretical model experimentally. In support of this, Weisell et al [44] found, from QM-modelling of pentamine 1,12-diamino-3,6,9-triazadodecane (SpmTrien) involving explicit water molecules, that 91% (HL p ) and 9% (HL s ) is formed with short chain being protonated preferentially (66% short and 25% long chain for the HL p form) which clearly contradicts all earlier as well recent studies whereas from the CEA of NMR data they obtained 94% (HL p ) and 6% (HL s ) with long chain, as expected, being protonated preferentially, ~84%. Moreover, note that their findings, in general, are not in agreement with other studies as they predicted a very small fraction of HL s whereas this tautomer was found to be significant in many polyamines and even dominating, e.g., in spermine [5,8,41].…”
Section: Theoretical Prediction Of Protonation Sequencementioning
confidence: 79%
“…To test this, explicit water molecules in computational modelling must be used. Even though this must be seen as extremely time-demanding modelling, we decided to embark on this project because (i) we can make use of an effective conformational search protocol developed and tested here as well as (ii) data generated at the B3LYP level were found here to be sufficient for the purpose of the study (the same level of theory was also used recently in modelling of SpmTrien [44]. Focusing now on analysis of d(H,H), we found the following:…”
Section: Theoretical Prediction Of Protonation Sequencementioning
confidence: 99%
“…23,24 This approach was refined to treat ionization of proteins and smaller molecules 18,25,26 and currently enjoys rapidly growing interest. 3,21,[27][28][29][30] The intrinsic description will be presented with examples of increasing complexity, thereby highlighting various strategies to extract the relevant parameters. We address the notion of group transferability, then the central idea of cluster expansion of the free energy, and finally molecular symmetries and homologous series.…”
Section: Introductionmentioning
confidence: 99%